Understanding our world in a time of crisis: Mathematics education pedagogy toward financial numeracy - Cavalcante, Alexandre; Savard, Annie (Universitas Papua, 2022)
This paper aims to address some implications for mathematics education regarding the financial and economic implications of the beginning of the COVID-19 pandemic. We use the term financial numeracy to refer to the quantitative aspect of financial education while also arguing for it to be considered a domain of mathematics education. Financial numeracy entails three dimensions: contextual, conceptual, and systemic. We bring three examples of financial implications of the crisis in different countries. Based on these examples, we constructed learning situations that reflect the distinct orientations of each dimension of financial numeracy to clarify the teaching of such a concept in school mathematics. Particularly in a time of crisis, mathematics education must address immediate needs of society as well as contribute to overcoming social challenges. We hope that financial numeracy brings innovative solutions to teach mathematics in a way that helps individuals and communities produce and manage resources while protecting the planet.